Association between Lifestyle and Gastroesophageal Reflux Disease Questionnaire Scores: A Cross-Sectional Study of 37 442 Chinese Adults - Yan Gong; Qiang Zeng; Yi Yan; Chaojing Han; Yansong Zheng (Gastroenterology Research and Practice)
The aim of this study was to investigate the distribution characteristics of GerdQ results in a Chinese population and the association between lifestyle and GerdQ scores. Among the 37 442 individuals enrolled from September 2009 to March 2016, 7 449 (19.89%) had a GerdQ score of ≥8 points and 29 993 (80.11%) had a GerdQ score of <8 points. The percentage of men with suspected GERD was significantly higher than the percentage of women with suspected GERD (χ2=111.571, P≤0.001), and the prevalence of GERD was higher in the young and middle-aged populations than in the elderly population. The prevalence of GERD increased gradually with weight gain (χ2=145.227, P≤0.001). With regard to lifestyle, the prevalence of GERD in the subjects who smoked (χ2=119.361, P≤0.001), consumed alcohol excessively, lacked physical activity (χ2=86.916, P≤0.001), and had an excessive intake of oil, meat, fish, and eggs showed an ascending trend (χ2=105.388, P≤0.001). In contrast, an adequate intake of vegetables (≥300 g/d) and fruit (≥200 g/d) was associated with a significantly lower incidence of GERD. Suspected GERD is very common in individuals undergoing health examinations. Unhealthy lifestyles are closely related to the high incidence of suspected GERD. GerdQ scores can play a role in screening for GERD.